Additive manufacturing of green composites: Poly (lactic acid) reinforced with keratin materials obtained from Angora rabbit hair - Flores‐Hernandez, Cynthia Graciela; Olivas Armendariz, Imelda; Velasco Santos, Carlos; Rivera Armenta, Jose Luis; Gómez Guzmán, Oscar; Yañez Limón, José Martín; López Barroso, Juventino; Martínez Hernandez, Ana Laura (2020)
In this research, additive manufacturing of polylactic acid (PLA) reinforced with keratin was studied. Keratin was obtained from Angora rabbit hair and modified with NaOH. Scanning electron microscopy (SEM) images showed that the modified surfaces were rougher than untreated surfaces. Furthermore, SEM images in the composites' fracture regions showed surface changes, associated with the nature of the reinforcement. Likewise, thermomechanical properties of the composites were attributed to the nature of the reinforcement and the type of keratin. Besides, the 3D printed composites showed higher thermal conductivity values than PLA with the addition of keratin. Cytotoxicity tests revealed an improvement in cell growth compared to the control and PLA. These results are meaningful toward the development of high thermal conductors and biocompatible composites with applications in different fields, where the use of only natural polymers is necessary.